If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 5j + -3 = 12 Reorder the terms: -3 + 5j = 12 Solving -3 + 5j = 12 Solving for variable 'j'. Move all terms containing j to the left, all other terms to the right. Add '3' to each side of the equation. -3 + 3 + 5j = 12 + 3 Combine like terms: -3 + 3 = 0 0 + 5j = 12 + 3 5j = 12 + 3 Combine like terms: 12 + 3 = 15 5j = 15 Divide each side by '5'. j = 3 Simplifying j = 3
| 3(2k-9)-2(k+5)= | | -5+10-2x=-60 | | 7(7x+5)=35+x | | (-5y^3x^2)(-6y^3x^3)(x^2)^-4/40x^3y^2(y^3)^2(x^3)^-2 | | 3-x/3=-7+16 | | 6x-3=4x-7 | | 23-5x=-5x-(1-8x) | | 5y-7x=6 | | -r=7 | | (10x^6+8x^4)/(2x^2)=14x^4 | | 23-5x=-5-(1-8x) | | y-19=-21 | | 6(4x-8)=2(9x+10) | | f(x+2)=7x+20 | | B/8=64 | | 5(x-4)+10=3+2(x-4) | | -5/9-2/3 | | 4.5+x=10 | | 3x*9+(24/8-15) | | 4(5n+3)=7n-27 | | 4y/3+y/15 | | -10/2-i | | 4b-8-b=10b-36 | | 0=t^2-6t-27 | | 3+8y=3y-12 | | -9y=-29 | | -4(5x-2y+5)= | | -25-8m=7-8(7m+4) | | -v/7=-52 | | 8-5x+9+2x=-4 | | 4/3q=7 | | 7n+12=-3 |